Sistem Informasi Uji Kelayakan Kendaraan Bermotor Berbasis Android (Studi Kasus pada CV. Axlindo Telematika Purwokerto) - Setyawati, Endang; Adilla, Axl; Purwono, Purwono; Wibowo, Adhi; Santoso, Muhammad Hery (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2026)
This study discusses the development of a motor vehicle roadworthiness test information system at CV. Axlindo Telematika Purwokerto, which was previously carried out manually through the registration process, testing, recapitulation, and issuance of KIR certificates. This manual system made the service ineffective and time-consuming. The solution developed was an ECU (Electronic Control Unit)-based Electronic Scanner with NodeMCU RS232 support that can automatically read test data and store it on a server for access via the web or Android applications. The development method used a prototype with REST API integration. The test results showed an increase in effectiveness of 98.9%, efficiency of 86.6%, usefulness of 82.2%, and a difference in data transmission time from 19.2 seconds to 1.39 seconds. The main contribution of this study is the design of hardware and software integration that can improve the accuracy and speed of KIR testing based on an intelligent information system.